2018
DOI: 10.3390/robotics7010003
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance and User-Centred Design of Assistive Exoskeletons for Older Adults: A Commentary

Abstract: Assistive robots are emerging as technologies that enable older adults to perform activities of daily living with autonomy. Exoskeletons are a subset of assistive robots that can support mobility. Perceptions and acceptance of these technologies require understanding in a user-centred design context to ensure optimum experience and adoption by as broad a spectrum of older adults as possible. The adoption and use of assistive robots for activities of daily living (ADL) by older adults is poorly understood. Olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…Older adults reported that they did not perceive the need for wearing an exoskeleton device despite their reported difficulties performing daily activities and their dependence on "traditional" mobility aids (see Figure 2). This paradoxical finding might be understood in light of previous work on Technology Acceptance Models (TAMs) that try to explain the complex relationship between the expectation of a person towards a technology (e.g., perceived usefulness and perceived ease of use) and their actual use [32]. It seems that older adults assess their health based on their current capabilities and assistive needs.…”
Section: Acceptance Of Exoskeleton Technology For Older Adultsmentioning
confidence: 96%
“…Older adults reported that they did not perceive the need for wearing an exoskeleton device despite their reported difficulties performing daily activities and their dependence on "traditional" mobility aids (see Figure 2). This paradoxical finding might be understood in light of previous work on Technology Acceptance Models (TAMs) that try to explain the complex relationship between the expectation of a person towards a technology (e.g., perceived usefulness and perceived ease of use) and their actual use [32]. It seems that older adults assess their health based on their current capabilities and assistive needs.…”
Section: Acceptance Of Exoskeleton Technology For Older Adultsmentioning
confidence: 96%
“…With the increasing research and societal interest in understanding factors that determine adoption in older patients, it is necessary to have a deeper insight into technology adoption through further research. This is evidenced by the evaluations of the Whole Systems Demonstrator (Shore, Power, de Eyto, & O'Sullivan, 2018). The demonstrator aims to build upon the existing qualitative evaluation in order to identify predictors of early removal of telehealth.…”
Section: Modelling Adoption Of Assistive Technologymentioning
confidence: 99%
“…Exoskeletons have potential applications in a wide variety of environments aside from healthcare too [25].…”
Section: Concept and Characteristicsmentioning
confidence: 99%
“…To decrease the abandonment and increase the acceptability of exoskeletons, a multi-disciplinary, universal, inclusive user-centered approach to better understand user needs with the development of person-environment-technology interaction should be addressed into the design process [76]. Additionally, research providing user insights may be useful to help understand and optimize the acceptance and adoption of such devices especially by older adults [25].…”
Section: Emotions As Part Of the Design Processmentioning
confidence: 99%